Population structure and regeneration of Tsuga dumosa and Abies spectabilis across altitudinal gradient in Rasuwa district, central Nepal - Dhungana, Badri Prasad; Thapa Chhetri, Vivek (Banko Janakari, 2024)
In Nepal, Tsuga dumosa thrives well between 2,100-3,600 m altitudes above the mean sea level, mostly in the temperate region while Abies spectabilis occurs between 3,000-4,200 m altitude above the mean sea level in the sub-alpine region. Research on mature T. dumosa-A. spectabilis forests in Nepal is limited. This study aimed to analyze the population structure and regeneration status of T. dumosa and A. spectabilis in the high-altitude mixed forests of Rasuwa, central Nepal. Conducted in 2023, a total of 61 concentric circular sample plots were laid out following a stratified systematic sampling method. The population-structure-curve displayed a consistent upward trend showing abnormality. The abnormal population structure with a lack of young trees and poor regeneration status in both species points towards potential threats like grazing and wildfires. The highest DBH class ranged from 90 cm to 120 cm DBH for T. dumosa while from 60 cm to 90 cm DBH for A. spectabilis. The study found that the seedling condition of T. dumosa species was ‘fair’ in the lower (2800-3100 m) and middle stratum (3100-3400 m), while it was ‘poor’ in the upper-elevation stratum (3400-3600 m). On the other hand, the seedling condition of A. spectabilis was found to be ‘poor’ in all the three elevation strata. Furthermore, the sapling condition of both the species were found to be ‘poor’. Therefore, the studied forest requires sustainable management along with a comprehensive strategy combining controlled grazing, zonation, monitoring, community engagement, regulation enforcement, restoration, ongoing research, and public awareness.